COMPARATIVE ASSESSMENT OF LONG-TERM RESULTS OF TREATMENT OF VESICOURETERAL REFLUX IN CHILDREN - Turaqulov , Zoirjon; Gafurov , Adxam; Tuychiyev , Golibjon (International Journal of Scientific Pediatrics, 2023)
Vesicoureteral reflux (VUR) is a severe disease of the urinary system in children. As a result, reflux nephropathy develops, which leads to a decrease in the size of the kidney, an increase in pyeloectasia, and gradual atrophy of the parenchyma with the development of chronic renal failure [2, 4, 6]. The traumatic nature of antireflux surgeries and the serious complications that arise after them force us to look for new solutions. With all the variety of methods of antireflux operations, the frequency of stenosis of the reimplanted ureter and recurrence of severe degrees of reflux, according to the literature, ranges from 3 to 40% [3, 5, 8]. Objective of the study: To study the results of endoscopic correction of VUR in children based on the analysis of clinical data, voiding cystourethrography, ultrasound research methods. Material and methods of research:The study presents data from 28 children who were treated in 2017-2022. in the Department of Urology of the Andijan Regional Children's Multidisciplinary Medical Center (ARCHMMC), on the basis of the Department of Pediatric Surgery, Andijan State Medical Institute (ASMI). The age of the patients was from 3 to 11. Mean age (5.1±3.1 years). Reflux was bilateral in 7 (33.3%) patients, unilateral in 14 (66.6%) patients. Of these, according to the data of voiding cystography, 17 (60.7%) were grade III, 11 (39.%) were grade IV. Boys were - 11 (39.2%) patients, girls - 19 (67.8%) patients. Results and conclusion: Endovesical correction of grade III-IV VUR is a reliable alternative to the choice of effective elimination of the defect. Endoscopic correction of VUR according to indications can be repeated. If multiple attempts at endoscopic correction of reflux are unsuccessful, the most effective treatment for primary VUR is open surgery - ureter neoimplantation according to the Cohen method.